2018
DOI: 10.1007/s00424-018-2133-0
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Ca2+ release decelerates mitochondrial cristae dynamics within the junctions to the endoplasmic reticulum

Abstract: Mitochondria are multifunctional organelles that essentially contribute to cell signaling by sophisticated mechanisms of communications. Live cell imaging studies showed that mitochondria are dynamic and complex structures that form ramified networks by directed movements, fission, and fusion events. There is emerging evidence that the morphology of mitochondria determines cellular functions and vice versa. Several intracellular signaling pathways and messengers including Ca2+ dynamically influence the archite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…The Presenilin-associated rhomboid-like (PARL) protease is involved in this OPA1-dependent protection, since Parl -/mice displayed reduced levels of S-OPA1 and PARL -/mitochondria exhibited accelerated cristae remodeling and cytochrome-c release during apoptosis (65). Knockdown of OPA1 in HeLa cells specifically reduced CM dynamics, whereas the IBM remained flexible (124). Recently, an elegant mechanistic framework was presented that integrates these earlier observations with the existence of OPA1 isoforms and OMA1/YME1L-mediated OPA1 processing (79)(80)(81).…”
Section: Mitochondrial Inner Membrane Fusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Presenilin-associated rhomboid-like (PARL) protease is involved in this OPA1-dependent protection, since Parl -/mice displayed reduced levels of S-OPA1 and PARL -/mitochondria exhibited accelerated cristae remodeling and cytochrome-c release during apoptosis (65). Knockdown of OPA1 in HeLa cells specifically reduced CM dynamics, whereas the IBM remained flexible (124). Recently, an elegant mechanistic framework was presented that integrates these earlier observations with the existence of OPA1 isoforms and OMA1/YME1L-mediated OPA1 processing (79)(80)(81).…”
Section: Mitochondrial Inner Membrane Fusionmentioning
confidence: 99%
“…In addition, various superresolution microscopy techniques (104,396) have been applied to mitochondrial (ultra)structural analysis (157). These include: structured illumination microscopy (124,358), 4Pi-confocal microscopy (94), STimulated Emission Depletion microscopy (158), Gated STimulated Emission Depletion microscopy (28), stochastic optical reconstruction microscopy (STORM), 3D-STORM, and direct STORM (146,178) and the ''Zernike Optimized Localisation approach in 3D'' (12). Unfortunately, the superresolution approaches that are currently available, have not been optimized for live-cell imaging and lack a sufficiently high acquisition rate (i.e., with low subsecond time resolution) and axial imaging depth to allow real-time analysis of mitochondrial ultrastructural dynamics in living cells (104).…”
Section: Quantification Of Mitochondrial Morphofunction In Living mentioning
confidence: 99%
“…The MICOS is localized at the intersection of the IMM and OMM, which results in the formation of membrane contact sites at cristae junctions (Friedman et al, 2015; Harner et al, 2011; Tarasenko et al, 2017; van der Laan et al, 2016). Ca 2+ is reported to modulate the cristae structure (Gottschalk et al, 2018; Greenawalt et al, 1964), however, no Ca 2+ -sensing protein has yet been identified as an essential component of the MICOS. To discern if MICU1 serves as a conduit for calcium-dependent regulation of the MICOS, we examined if genetic loss of MICU1 had any effect on mitochondrial ultrastructure and cristae junctions.…”
Section: Resultsmentioning
confidence: 99%
“…The dynamics of the IMM in regions of close mitochondria–ER contact could be analyzed, for instance. While silencing of OPA1 reduced IMM kinetics globally, ER Ca 2+ release decreased IMM kinetics exclusively in mitochondrial areas in close proximity to the ER, pointing to a Ca 2+ ‐regulated mechanism of IMM rearrangement . The submitochondrial dynamic and MICU1‐dependent relocalization of mitochondrial Ca 2+ uniporter (MCU) and UCP2 upon ER‐Ca 2+ release form the entire IMM into the inner boundary membrane, which was visualized recently using SIM .…”
Section: Mitochondria As Highly Specialized Working Unitsmentioning
confidence: 96%
“…Therefore, STED or SIM microscopy have been used to image, for instance, binding of fluorescent dyes dependent on Δψ m , such as Mitotracker Green FM and tetramethylrhodamine methyl ester (TMRM), to the IMM. By using these techniques, cristae structure can be resolved and dynamic rearrangement of the IMM can be investigated due to high temporal resolution . The dynamics of the IMM in regions of close mitochondria–ER contact could be analyzed, for instance.…”
Section: Mitochondria As Highly Specialized Working Unitsmentioning
confidence: 99%